Criatividade na primeira infância: potencialidades expressivas dos bebês na Educação Infantil - Calsone, Júlia Santos Abichabki (Universidade Federal de São Carlos, 2025)
This study aims to investigate how creativity manifests in infants and how it can be either enhanced or inhibited by everyday pedagogical practices in Early Childhood Education. This bibliographic research is grounded in the understanding that creativity is a universal human capacity, present from the earliest years of life and closely connected to play, imagination, and the free exploration of the world. Based on authors who address the topic, the study discusses the educator’s role in mediating creative experiences, the impact of electronic intoxications on child development, and the importance of creativity for later stages of life. It concludes that fostering creative expression from early childhood is an ethical and political task of contemporary pedagogy, aimed at forming sensitive, autonomous individuals capable of transforming reality.
Creativity in early childhood: babies' expressive potential in early Childhood Education
Keywords: Criatividade; Educação Infantil; Bebês; Imaginação; Brincar; Creativity; Early Childhood Education; Babies; Imagination; Play; CIENCIAS HUMANAS::EDUCACAO